DEM simulation of particles of complex shapes using the multisphere method: Application for additive manufacturing - Ribeiro Parteli, Eric Josef (AIP Conference Proceedings, 2013)
Additive manufacturing constitutes a promising production technology with potential application in a broad range of industrial areas. In this type of manufacturing process, objects are created from powder particles by adding layers of material upon one another through selectively melting particles from the powder bed. However, understanding the mechanical behavior of the powder during manufacturing as a function of material properties and particle shape is an essential pre-requisite for optimizing the production process. Here we develop a numerical tool for modeling the dynamics of powder particles during additive manufacturing based on force-based simulations by means of the Discrete Element Method (DEM). An existing DEM software (LIGGGHTS) is extended in order to study the transport of powder particles of complex geometric shapes through accounting for the boundary conditions inherent to the manufacturing proces
Keywords: additive manufacturing; DEM simulation; granular materials; multisphere method